2013
DOI: 10.1155/2013/283472
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and Lead Uptake by Vegetable Crops Grown on Historically Contaminated Orchard Soils

Abstract: Transfer of Pb and As into vegetables grown in orchard soils historically contaminated by Pb arsenate pesticides was measured in the greenhouse. Lettuce, carrots, green beans and tomatoes were grown on soils containing a range of total Pb (16.5–915 mg/kg) and As (6.9–211 mg/kg) concentrations. The vegetables were acid-digested and analyzed for total Pb and As using ICP-mass spectrometry. Vegetable contamination was dependent on soil total Pb and As content, pH, and vegetable species. Arsenic concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…Consistent with results from other studies (McBride et al 2012; 2014), the tissue Pb and Al concentrations were significantly correlated (r = 0.574, p<0.05), an indication that soil particle contamination of the foliage probably accounted for many of the elevated Pb levels measured in field-grown lettuce. The high clay and exchangeable base cation content, as well as the generally non-acid nature of the orchard soils from this site, maintain soluble and phytoavailable Pb at very low concentrations in this soil (McBride, 2013). Physical contamination (soil particle adherence) may therefore be the most important mechanism of Pb transfer to the leafy and root crops in particular.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with results from other studies (McBride et al 2012; 2014), the tissue Pb and Al concentrations were significantly correlated (r = 0.574, p<0.05), an indication that soil particle contamination of the foliage probably accounted for many of the elevated Pb levels measured in field-grown lettuce. The high clay and exchangeable base cation content, as well as the generally non-acid nature of the orchard soils from this site, maintain soluble and phytoavailable Pb at very low concentrations in this soil (McBride, 2013). Physical contamination (soil particle adherence) may therefore be the most important mechanism of Pb transfer to the leafy and root crops in particular.…”
Section: Resultsmentioning
confidence: 99%
“…Stilwell et al (2006) measured high concentrations of As in some crops (arugula and chives) but not others grown on soils contaminated by As from pressure-treated wood. Our results from greenhouse studies to date reveal substantial risk of exceeding international standards for vegetable crops when soil total As exceeds 100 mg kg −1 and Pb exceeds 400 mg kg −1 (McBride 2013). Nevertheless, there is still insufficient basic knowledge to make even approximate predictions of As or Pb content for a wide range of crops grown on soils with different properties.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Though available data are limited, when the number of environmental and soil variables is reduced, as is done with single-site field studies and greenhouse research with one particular soil containing a range of Pb concentrations, a clearer relationship between vegetable Pb and soil Pb emerges (McBride, 2013; and unpublished results).…”
Section: Introductionmentioning
confidence: 99%
“…Farooqi et al studied that amount of arsenic in soil surface samples was 10.2 mg/kg, with highest concentration 35 mg/kg [12]. McBride grew green beans, lettuce, carrot and tomatoes on soil containing a range of total as (6.9-211 mg/kg) concentrations [13]. He found that arsenic concentration highest in lettuce and green beans.…”
Section: Introductionmentioning
confidence: 99%